The Role of Heterovalent P+5/Si+4 Substitution on the Microhardness of Ag6+x(P1-xSix)S5I Single Crystals - Shender, I.O.; Filep, M.J.; Kokhan, O.P.; Bilanych, V.S.; Pogodin, A.I.; Malakhovska, T.O. (Physics and Chemistry of Solid State, 2026)
The dependence of the microhardness of Ag6+x(P1-xSix)S5I (х = 0.25; 0.5; 0.75) single crystals on load and composition was investigated using the Vickers method. The investigation was performed in wide range of the applied loads 0.05…2 N at room temperature. It has been established that an increase in the load on the indenter leads to a nonlinear decrease in the microhardness values for all studied crystals. Observed dependences indicates a normal indentation size effect. The behavior of microhardness of Ag6+x(P1-xSix)S5I single crystals were described using the geometrically necessary dislocations model. The corresponding parameters of the used model were determined. The influence of ionic radii and electronegativity on microhardness change were discussed. Using Meyer's law, the occurrence of a normal indentation size effect has been confirmed.